МОРСКИЕ ПОБЕРЕЖЬЯ РОССИЙСКОЙ ФЕДЕРАЦИИ И ИХ ПРАВОВАЯ ЗАЩИТА - Пастушкова С.А. (My University, 2006)
Development of the normative laws, bylaws, restrictions, and orders regulating the use and conservation of coastal zone is the main component of the seashores protection. In the draft federal law "On the seashores of the Russian Federation" the seashore is treated as substantive object of law space, having strict spatial boundaries and explicit regime of exploitation. The enactment of a bill will benefit the environmental and social condition of the seashore zone, will mitigate the collisions between different users of its natural resources.
Keywords: 551.4.435.36(470)